A teoria freudiana do fênomeno moral e a filosofia moral de Kant: é o superego um imperativo categórico? - Lara, Luciana Maccari (Universidade do Vale do Rio do Sinos, 2006)
This work intends to make use of Kant’s moral philosophy, specially the concept of autonomy, in order to get a better unsderstanding of Freud’s moral phenomenon theory, what means the superego theory. Aiming at this purpose, the work proposes three questions: a) what’s the legitimacy of a moral psychic instance as a concept of a theory that has in its basis the unconscious determinism? b) what’s the adequacy of the Freud’s parallel between the superego and Kant’s categorical imperative? c) what’s the use of Kant’s moral philosophy to a better understanding of Freud’s superego theory? The work tries to demonstrate the limitation of Freud’s parallels between the superego and the categorical imperative, considering that this paralles occurs in a moment of elaboration of the superego concept. It also looks to emphasize the shared bases of both Freud and Kant theories in the iluministic concept of reason, and the consequences of this fact for Freud’s superego theory, specially in order to answer the question: is
Keywords: autonomia; razão; superego; moral; autonomy; reason; superego; moral; Ciências Humanas